The application of mixed reality technique in oromaxillo-facial reconstruction with the perforator flap for malignant tumor patients - Liu, Yixiu; Wu, Jian; Liu, Daide; Xiang, Dalan; Wu, Xiaoyue; Wang, Ting (Frontiers in Oncology, 2024)
Objectives: The integration of quantitative imaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI) with mixed reality (MR) technology holds promise for enhancing the diagnosis, prognosis, and treatment monitoring of cancer. This study compares the characteristics and effects of MR and color Doppler ultrasound (CDU) in the localization of perforator blood vessels in the lower extremities.Methods: Two techniques were used to locate the perforator vessels in 40 cases of maxillofacial defect repair using perforator flaps from the lower extremities. The number of perforator vessels located in the flap area and the actual number of perforator vessels explored during the surgery were recorded. The recognition rate was calculated and the operation time and blood loss were recorded for each case.Results: The recognition rates of MR technology and CDU in perforating vessels of the lower limbs were 93.9% and 97.2%, respectively (p > 0.05). The operation time was 52-74 minutes, 65-88 minutes (p > 0.05). The average bleeding volumes were 24 and 56 ml (p < 0.05), respectively. All perforator flaps were alive. One flap had a crisis and recovered after emergency exploratory treatment. Thirty donor sites of the lower extremities were directly sutured, and wounds were closed by abdominal skin grafting in 10 cases.Conclusions: MR technology for successfully identifying perforator vessels can shorten the operation time, reduce the amount of bleeding in the donor site, and reduce trauma to the donor site.